Fuel to the fire : how Trump made America's broken foreign policy even worse (and how we can recover) - Glaser, John (Author); Preble, Christopher A.; Thrall, A. Trevor (Cato Institute, 2019)
"As a presidential candidate, Donald Trump broke not only from the Republican Party but also from the bipartisan consensus on the direction of recent U.S. foreign policy. Calling the Iraq War a terrible mistake and lamenting America's nation-building expeditions, Trump evinced little interest in maintaining the traditional form of American leadership of the liberal international order. Instead, Trump's "America First" vision called for a reassertion of American nationalism on the economic front as well as in foreign affairs. Since Trump took office, it has become clear that America First was more of a campaign slogan than a coherent vision of American grand strategy. As president, Trump has steered a course that has maintained some of the worst aspects of previous foreign policy-namely, the pursuit of primacy and frequent military intervention-while managing to make a new set of mistakes all his own. While President Trump continues to muddle along, now is the time to consider what should come after him. In Fuel to the Fire, the authors characterize and explain Trump's foreign policy doctrine and the effect that he likely will have on U.S. foreign policy during his tenure. Furthermore, they provide policy recommendations for the future centered on restraint-a radical departure from America's current expansive global military role in the world, but a return to the historical American focus on trade and diplomacy"--